Perencanaan Drainase pada Kawasan Kumuh Kabupaten Kutai Barat, Kecamatan Barong Tongkok - Ruslan, Ruslan; Assiddieq, Moch; Rosdiana, Rosdiana (Universitas Muhammadiyah Kendari, 2026)
This study aims to design an effective drainage system to reduce waterlogging in the residential area of Barong Tongkok District, Kutai Barat Regency. The analysis combines rainfall data, land-use conditions, and physical characteristics of the study area. Design rainfall was calculated using the Log Pearson Type III distribution, rainfall intensity using the Mononobe method, and peak discharge using the Rational Method. The results show that the design flood discharge for a 10-year return period is 1.203 m³/s. Using Manning’s equation, a trapezoidal channel with a 0.65 m bottom width, 1.00 m depth, and 0.27 side slope has a flow capacity of 1.33 m³/s. This indicates that the planned drainage channel can accommodate the design discharge and is suitable for implementation in the study area. The proposed design is expected to improve drainage performance and reduce flood risks in Barong Tongkok District.